2005
DOI: 10.1038/sj.mp.4001764
|View full text |Cite
|
Sign up to set email alerts
|

Identification of additional variants within the human dopamine transporter gene provides further evidence for an association with bipolar disorder in two independent samples

Abstract: The dopamine transporter (DAT) is the site of action of stimulants, and variations in the human DAT gene (DAT1) have been associated with susceptibility to several psychiatric disorders including attention deficit hyperactivity disorder (ADHD) and bipolar disorder. We have previously reported the association of bipolar disorder to novel SNPs in the 3 0 end of DAT1. We now report the identification of 20 additional SNPs in DAT1 for a total of 63 variants. We also report evidence for association to bipolar disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…Furthermore, we expanded the predictive validity of the model by the determination of Li preventive effects. Numerous findings from clinical studies highlight the importance of DAT in BD pathophysiology: i) a singlenucleotide polymorphism (SNP) in the rs27072 affecting DAT mRNA expression and translation was significantly associated with BD (Pinsonneault et al 2011) as well as the presence of multiple variants in DAT1 was noticed to convey susceptibility to BD (Greenwood et al 2006); ii) a decrease in DAT mRNA levels was demonstrated in the postmortem frontal cortex of BD patients as compared to healthy controls (Rao et al 2012) and iii) significant lower DAT availability relative to healthy controls was observed in the bilateral dorsal caudate of unmedicated BD patients that underwent PET imaging with the DAT-selective radiotracer [(11) C]CFT and a structural magnetic resonance imaging (MRI) scan (Anand et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we expanded the predictive validity of the model by the determination of Li preventive effects. Numerous findings from clinical studies highlight the importance of DAT in BD pathophysiology: i) a singlenucleotide polymorphism (SNP) in the rs27072 affecting DAT mRNA expression and translation was significantly associated with BD (Pinsonneault et al 2011) as well as the presence of multiple variants in DAT1 was noticed to convey susceptibility to BD (Greenwood et al 2006); ii) a decrease in DAT mRNA levels was demonstrated in the postmortem frontal cortex of BD patients as compared to healthy controls (Rao et al 2012) and iii) significant lower DAT availability relative to healthy controls was observed in the bilateral dorsal caudate of unmedicated BD patients that underwent PET imaging with the DAT-selective radiotracer [(11) C]CFT and a structural magnetic resonance imaging (MRI) scan (Anand et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This drug is metabolically converted in humans to its close related analog GBR 12935 (Brown and Chand 2010), a drug also known as a DAT inhibitor (Andersen 1987). Importantly, the GBR12909-induced model of mania is based on the putative aetiology of BD, in which polymorphisms in the human DAT have been associated with the bipolar endophenotype (Greenwood et al 2006;Pinsonneault et al 2011). Conversely, mice generated through genetic deletion of DAT (DAT-KO) (Barr et al 2004) or with reduced DAT functioning (DAT-KD) (Young et al 2011b) exhibit hyperdopaminergic tone and hyperlocomotion resembling BD mania.…”
Section: Introductionmentioning
confidence: 98%
“…Patients were administered the Young Mania Rating Scale (YMRS) to quantify manic symptoms. Patients' blood samples were analyzed for the COMT Val158Met polymorphism per established methods [3]. Of the 26 patients, 6 were genotyped as Met/Met, 10 as Val/Val, and 10 as Val/Met heterozygotes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the mania of bipolar disorder (BD) may be influenced by dysregulation of the dopamine (DA) system, and blocking DA reuptake (the DA transporter; DAT) models several aspects of mania in animals [2]. Accordingly, genes that regulate synaptic DA reuptake such as the DAT gene have been linked with BD [3]; however, the influence of other synaptic DA clearance-related genes on phenotypes of BD has been relatively understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Excess dopamine has also been reported to decrease inhibition of stimuli from the surrounding environment [182,183], which is characteristic of both creativity [71] and psychosis [184,185,186]. Interestingly, the DAT gene ( SLC6A3 ) has shown evidence of association and linkage with bipolar disorder [187,188,189], schizophrenia [190], neurocognitive deficits in schizophrenia [191], and, of particular relevance, sensorimotor gating deficits in schizophrenia [192,193]. Furthermore, decreased thalamic D2 receptor densities are observed both in patients with psychosis [194,195,196] and in healthy subjects with high divergent thinking scores [197,198].…”
Section: Molecular Pathways and Genetic Linksmentioning
confidence: 99%